2019
DOI: 10.1007/s11356-019-04440-7
|View full text |Cite
|
Sign up to set email alerts
|

Modelling aggregate exposure to pesticides from dietary and crop spray sources in UK residents

Abstract: Human exposure to pesticide mixtures can occur from the diet and other sources. Realistic exposure and risk assessments should include multiple sources and compounds and include the relative hazards of the different compounds. The EU-funded Euromix project is developing new web-based tools to facilitate these calculations. A case study is presented that exemplifies their use for a population of UK residents, including exposure from crop-spraying. A UK pesticide usage survey provided information on real pestici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Dietary mixture exposures can be calculated from data from food and drinking water surveys, as was done in a case study in the EuroMix project, for pesticides with relevance to the CAG Steatosis, 53 eventually refined through modeling of aggregate exposure from nondietary sources in addition to dietary sources. 54 , 55 Another approach to estimate exposure is human biomonitoring, through analysis of CAG-specific contaminants and their metabolites in human biomaterial, particularly urine and blood. 56 , 57 , 58 Such information, combined with analysis of potential sources of the measured contaminants, can help to build and refine physiologically based pharmacokinetic models for estimating internal human exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary mixture exposures can be calculated from data from food and drinking water surveys, as was done in a case study in the EuroMix project, for pesticides with relevance to the CAG Steatosis, 53 eventually refined through modeling of aggregate exposure from nondietary sources in addition to dietary sources. 54 , 55 Another approach to estimate exposure is human biomonitoring, through analysis of CAG-specific contaminants and their metabolites in human biomaterial, particularly urine and blood. 56 , 57 , 58 Such information, combined with analysis of potential sources of the measured contaminants, can help to build and refine physiologically based pharmacokinetic models for estimating internal human exposure.…”
Section: Discussionmentioning
confidence: 99%
“…e. Non-dietary exposure models (e.g. Kennedy et al, 2019 The present document has been produced and adopted by the bodies identified above as authors. In accordance with Article 36 of Regulation (EC) No 178/2002, this task has been carried out exclusively by the authors in the context of a grant agreement between the European Food Safety Authority and the authors.…”
Section: Supra-modular Modelsmentioning
confidence: 99%
“…Aggregated exposure models a. Aggregate or multiple route exposure model for single and multiple substances (Karrer et al, 2019b;Kennedy et al, 2019 b. Assessment group construction and membership model (Kennedy et al, 2020).…”
Section: Supra-modular Modelsmentioning
confidence: 99%